Cloning and sequence analysis of cDNAs encoding precursors of urotensin II-alpha and -gamma - Ohsako, S (J Neurosci, 1986)
The primary structures of the precursors of urotensin II (UII)-alpha and -gamma, neuropeptide hormones of the caudal neurosecretory system of the carp, Cyprinus carpio, have been determined by analyzing the nucleotide sequences of cloned DNAs complementary to the mRNAs encoding them. A cDNA library, constructed with poly(A)+RNA in the preterminal spinal cord, was screened using 32P-labeled synthetic oligonucleotides representing all possible cDNA sequences corresponding to the pentapeptide common to all forms of carp UII (UII-alpha, -beta, and - gamma). Twenty out of 39 positive clones were analyzed with the restriction endonucleases, HindIII and PvuII, and classified into 4 groups. Nucleotide sequence analysis of 4 clones representing each group revealed that 2 clones encode the precursor of UII-alpha and the other 2 that of UII-gamma. Both precursors consist of 125 amino acid residues, and UII-alpha and -gamma exist at the carboxyl-termini preceded by Arg-Lys-Arg. The homology in both nucleotide and amino acid sequences between the precursors of UII-alpha and -gamma is more than 90%, suggesting that the genes were generated from a common ancestral gene by duplication. There is no sequence homology between the precursors of UII and urotensin I, another peptide hormone of the caudal neurosecretory system, nor between the precursors of UII and somatostatin-14. RNA transfer blot analysis indicated that mRNAs encoding the precursors of UII-alpha and -gamma are present in the spinal cord but not in the brain, intestine, liver, or kidney of the carp.(ABSTRACT TRUNCATED AT 250 WORDS)